Multiple dsRNases Involved in Exogenous dsRNA Degradation of Fall Armyworm Spodoptera frugiperda - Yao, Yang; Lin, Dong-Jiang; Cai, Xiang-Yun; Wang, Ran; Hou, You-Ming; Hu, Chao-Hua; Gao, San-Ji; Wang, Jin-Da (Frontiers in Physiology, 2022)
RNAi is regarded as a promising technology for pest control. However, not all insects are sensitive to RNAi. Studies have confirmed that insect dsRNases are one of key factors affecting RNAi efficiency. In the current study, we identified four genes coding for dsRNases from the Spodoptera frugiperda genome. Spatial and temporal expression analysis showed that those dsRNases were highly expressed in the midgut and old larvae. Then a delivery method was applied for inducing efficient RNAi based on dsRNA encapsulated by liposome. Furthermore, we assessed degradation efficiency by incubation with dsRNA with gut juice or hemocoel to characterize potential roles of different SfdsRNases after suppression of SfdsRNase. The result showed that interferenced with any sfdsRNase reduced the degradation of exogenous dsRNA in midgut, interfered with sfdsRNase1 and sfdsRNase3 slowed down the degradation of exogenous dsRNA in hemolymph. Our data suggest the evolutionary expansion and multiple high activity dsRNase genes would take part in the RNAi obstinate in S. frugiperda, besides we also provide an efficient RNAi method for better use of RNAi in S. frugiperda.